Nine-Phase Induction Motor Dynamic Model Based On 3x9 Transformation Matrix - Arman Jaya; Soebagio Soebagio; Mauridhi Hery Purnomo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
Analysis of the dynamic model nine-phase induction motor becomes difficult because based on a 9x9 matrix and a circuit of magnetically coupled transformer. In order to gain the qdn dynamic model of the nine-phase induction motors in easy, simple, quick and consistent way, the motor analysis will  based on 3x9 transformation matrix and the equivalent circuit T model. The 3x9 transformation matrix qdn is substituted into the equation in  form abc so that the matrix equation of qdn is obtained. Then qdn equation results a similar qd equivalent circuit, which has different methods n that is, based the circuit of magnetically coupled transformer. Simulation results show that the dynamic characteristics of 9-phase induction motor based on the T model and magnetically coupled circuit have similar torque and speed dynamic response.